A pilot study of Practice While Watch based 50 min school quality cardiopulmonary resuscitation classroom training: a cluster randomized control trial - Tanaka, Shota (Acute Med Surg, 2019)
AIM: Cardiopulmonary resuscitation (CPR) training in schools can increase the rate of bystander CPR. We assessed whether a “Quality CPR (QCPR) Classroom” can support CPR performance by students trained by a teacher who is not a CPR instructor. METHODS: A cluster randomized trial was undertaken to assess the effectiveness of a 50‐min Practice While Watch CPR training program enhanced by QCPR Classroom, which used 42 manikins connected by Bluetooth to real‐time feedback monitoring. Fifty‐seven students were divided into Group 1, taught by a non‐CPR‐instructor, and Group 2, taught by a CPR instructor. Psychomotor and cognitive tests were administered before and after training. Primary outcomes were post‐training compression depth and rate and percent of improvement in adequate depth, recoil, and overall score. The secondary outcome was risk improvement. RESULTS: Post‐training, Group 1 achieved 62.1 ± 7.7 mm and 118.0 ± 3.6 compressions/min whereas Group 2 achieved 57.4 ± 9.8 mm and 119.8 ± 5.4 compressions/min. The overall score improvement in percentage points was 36.4 ± 25.9% and 27.0 ± 27.7%, respectively (P ≤ 0.001 for both). The adequate depth improvement in percentage points was 22.4 ± 35.4% and 32.5 ± 40.0%, respectively (P = 0.33). Teaching by a non‐CPR instructor improved student cognitive knowledge. CONCLUSIONS: Using a QCPR Classroom to enhance CPR teaching by a non‐CPR‐instructor results in similar or better outcomes compared to using a CPR instructor. Use of a Practice While Watch QCPR Classroom will provide adequate quality in preparing students for CPR.